New soft materials based on boron compounds
By introducing metal boron cluster salts and soft solid matrix into soft solid electrolytes to form electrolytes with high entropy and plastic or glass-like molecular structures, the low melting point and temperature window limitations of existing electrolytes in terms of high conductivity are solved, and high ionic conductivity and flexibility are achieved.
Patent Information
- Application Number
- JP2020093483
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-05-29
- Filing Date
- 2020-05-28
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2040-05-28
AI Technical Summary
The existing solid electrolytes based on organic ion liquid crystals have low melting point and temperature window limitations in terms of high conductivity, which limits their application range.
Using a combination of soft solid electrolytes containing metal boron clusters, an electrolyte with high entropy and plastic or glass-like molecular structure is formed by introducing metal boron cluster salts and soft solid matrix into the soft solid electrolyte.
It is achieved with high ionic conductivity similar to organic ionic liquid crystal electrolyte without relying on solid-state phase transition, while improving the softness and stability of the electrolyte.
Smart Images

Figure 0007653002000002 
Figure 0007653002000003 
Figure 0007653002000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates generally to soft solid-state electrolytes for use in secondary batteries and relates to boron cluster chemistry. [Background technology]
[0002] Solid-state electrolytes offer many advantages in the design of secondary batteries, including mechanical stability, non-volatility, and ease of manufacture. Current inorganic solid-state electrolytes that exhibit high ionic conductivity are mostly hard materials that cannot maintain significant contact with the electrode materials during repeated use of the battery. Organic solid-state electrolytes, such as polymers, solve the latter problem due to their reduced hardness. However, they have poor ionic conductivity. Summary of the Invention [Problem to be solved by the invention]
[0003] These solid electrolytes with significant ionic conductivity are generally based on organic ionic liquid crystals (OIPCs). These materials rely on solid-solid phase transitions to achieve high conductivity. OIPC-based materials can have challenges, such as low melting points and / or low temperature windows of the conductive phase, which limit the applicability of OIPC-based materials.
[0004] It would therefore be desirable to provide improved solid-state electrolytes that match the conductivity of OIPC-based electrolytes, but do not rely on limiting phase transitions. [Means for solving the problem]
[0005] This section provides a general summary of the disclosure and is not a comprehensive disclosure of the entire scope or all features of the disclosure.
[0006] In one aspect, a solid electrolyte composition for use in a secondary battery is disclosed. The electrolyte composition is represented by the formula G p The electrolyte composition comprises a soft solid matrix of A, G is an organic cation selected from the list of possible cations, p is 1 or 2, and A is a boron cluster anion. The electrolyte composition further contains a metal salt having a metal cation and a metal salt anion. The metal salt anion may optionally be a boron cluster anion, which may be the same as or different from the boron cluster anion, A, of the soft solid matrix described above.
[0007] In one embodiment, the boron cluster anion of the soft solid matrix, A, the boron cluster anion of the metal salt, if present, or the boron cluster anions, are each independently defined by any of the following anionic formulas: [B y H (y-z-i) R z X i ] 2- , [CB (y-1) H (y-z-i) R z X i ] - , [C2B (y-2) H (y-t-j-1) R t X j ] - , [C2B (y-3) H (y-t-j) R t X j ] - , or [C2B (y-3) H (y-t-j-1) R t X j ] 2- In various embodiments, y can be an integer ranging from 6 to 12, (z+i) can be an integer ranging from 0 to y, (t+j) can be an integer ranging from 0 to (y-1), and X can be F, Cl, Br, I, or a combination thereof. R can be an organic substituent, hydrogen, or a combination thereof.
[0008] These and other features of the soft electrolyte, e.g., OIPC, and the method of manufacturing electrochemical cells having the same will become apparent from the following detailed description taken in conjunction with the figures and examples, which are intended to be illustrative and not exhaustive.
[0009] Various aspects and advantages of the present invention will be apparent and further understood from the following description of the embodiments taken in conjunction with the accompanying drawings. [Brief description of the drawings]
[0010] [Figure 1A] FIG. 1A is a perspective schematic diagram of a representative boron cluster anion, closo-[B12H12]2-, of the present disclosure. [Figure 1B] FIG. 1B is a perspective schematic diagram of the boron cluster anion, closo-[CB11H12]-, of the present disclosure. [Figure 1C] FIG. 1C is a perspective schematic diagram of the boron cluster anion, closo-[C2B10H12]-, of the present disclosure. [Figure 2A] FIG. 2A is a plot of differential scanning calorimetry (DSC) data for a soft solid matrix (solid matrix) electrolyte of the present disclosure, N-methyl-N-butylpyrrolidinium closo-[CB11H12]-. [Figure 2B] FIG. 2B is a plot of differential scanning calorimetry (DSC) data for triethylhexylphosphonium closo-[CB11H12]-doped with a solid matrix of the present disclosure, LiCB11H12. [Diagram 3] FIG. 3 is a plot of the ionic conductivity of several solid matrices of the present disclosure, each having the closo-[CB11H12]-anion. [Figure 4] FIG. 4 is a plot showing conductivity as a function of temperature for a solid matrix according to the present disclosure at two applied pressures. [Diagram 5]FIG. 5 is a plot of ionic conductivity in N-methyl-N-butylpyrrolidinium CB11H12 doped with LiCB11H12, and the inset is a photographic image of the soft electrolyte. [Figure 6] FIG. 6 is a plot of the ionic conductivity of different soft electrolytes of the present disclosure having a 1:1 molar ratio of LiCB9H10:LiCB11H12 in N-methyl-N-butylpyrrolidinium CB9H10 or N-methyl-N-butylpyrrolidinium CB11H12. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present disclosure provides soft electrolyte compositions similar to organic ionic liquid crystals (OIPCs), which are typically solid at battery operating temperatures but have very high ionic conductivity due to their high-entropy, plastic-like molecular structure.
[0012] The soft electrolyte composition of the present disclosure includes a metal boron cluster salt and a soft solid matrix (solid matrix) doped with the salt. The solid matrix contains boron cluster anions and organic cations with flexible and / or asymmetric substituents. The resulting electrolyte forms a soft solid with a plastic or glass-like, high entropy molecular structure, which results in high ionic mobility and conductivity.
[0013] Accordingly, a soft solid electrolyte composition (hereinafter simply referred to as the "electrolyte composition") for use in a secondary battery is disclosed. The electrolyte composition has the formula G p The solid matrix comprises A, where G is an organic cation, A is a boron cluster anion, and p is 1 or 2. In one embodiment, the organic cation comprises at least one of an ammonia cation and a phosphonium anion, for example, as illustrated in Structures 1-4 below.
[0014] [ka]
[0015] wherein R and R', and R'' and R''', if present, are each independently a substituent belonging to any of the following: group (i) linear, branched, or cyclic C1-C8 alkyl or fluoroalkyl groups; group (ii) C6-C9 aryl or fluoroaryl groups; group (iii) linear, branched, or cyclic C1-C8 alkoxy or fluoroalkoxy groups; group (iv) C6-C9 aryloxy or fluoroaryloxy groups; group (v) amino; and group (vi) a substituent having two or more moieties defined by any two or more of groups (i) to (v). The substituents R and R', and R'' and R''', if present, may alternatively be referred to hereinafter as "multiple organic substituents". In general, organic cations will have a degree of asymmetry with respect to the size and distribution of the substituents. Thus, at least one of R, R', R'' and R''' is different from the others, and the cation preferably does not contain two pairs of substituents.
[0016] In certain particular embodiments, the organic cation may be selected from the group comprising: N-methyl-N-propylpyrrolidinium (hereinafter referred to as "Pyr13"); N-methyl-N,N-diethyl-N-propylammonium (N1223); N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium (DEME); N-methyl-N-propylpiperidinium (hereinafter referred to as "Pip13"); N-methyl-N-(2-methoxyethyl)-pyrrolidinium (Pyr12ol); trimethylisopropylphosphonium (P111 i4); methyltriethylphosphonium (P1222); methyltributylphosphonium (P1444); N-methyl-N-ethylpyrrolidinium (Pyr12); N-methyl-N-butylpyrrolidinium (Pyr14); N,N,N-triethyl-N-hexylammonium (N2226); triethylhexylphosphonium (P2226); and N-ethyl-N,N-dimethyl-N-butylammonium (N4211). It should also be understood that in some embodiments, G can contain more than one of the above cations. It should also be understood that when p is 2, the two organic cations contained in the stoichiometric unit of the solid matrix can be the same cation or two different cations.
[0017] As used herein, the term "boron cluster anion" generally refers to any of the following anionic forms: boranes having 6-12 boron atoms with a total charge of -2; carboranes having one carbon and 5-11 borons in the cluster structure with a total charge of -1; carboranes having two carbon atoms and 4-10 boron atoms in the cluster structure with a total charge of -1 or -2. In some variations, the boron cluster anion may be unsubstituted and may have only hydrogen atoms in addition to the above. In some variations, the boron cluster anion may be substituted and may have one or more halogens in place of one or more hydrogen atoms; one or more organic substituents in place of one or more hydrogen atoms; or combinations thereof.
[0018] In certain embodiments, the boron cluster anion may be an anion represented by any of the following formulas: [B y H (y-z-i) R z X i ] 2- Anionic Formula I, [CB (y-1) H (y-z-i) R z X i ] - Anionic Formula II, [C2B (y-2) H (y-t-j-1) R t X j ] - Anionic Formula III, [C2B (y-3) H (y-t-j) R t X j ] - Anionic Formula IV, or [C2B (y-3) H (y-t-j-1) R t X j ] 2- Anionic formula V, where y is an integer ranging from 6 to 12; (z+i) is an integer ranging from 0 to y; (t+j) is an integer ranging from 0 to (y-1); and X is F, Cl, Br, I, or a combination thereof. The substituent R in the anionic formulas I to V may be any organic substituent or hydrogen.
[0019] X may be F, Cl, Br, I, or a combination thereof, where i is an integer ranging from 2 to y, or j is an integer ranging from 2 to (y-1), meaning that there are multiple halogen substituents. In such cases, the multiple halogen substituents may include F, Cl, Br, I, or any combination thereof. For example, in a boron cluster anion having three halogen substituents (i.e., when i or j is 3), the three halogen substituents may be three fluorine substituents; one chlorine substituent, one bromine substituent, and one iodine substituent; or any other combination.
[0020] In many embodiments, the boron cluster anion can include either a substituted or unsubstituted closo-boron cluster anion. In some embodiments, the boron cluster anion is closo-[B6H6] 2- , closo-[B 12 H 12 ] 2- , closo-[CB 11 H12 ] - , or closo-[C2B 10 H 11 ] - and other closo-boron cluster anions.
[0021] 1A-1C show exemplary structures of unsubstituted boron cluster anions according to anionic formulas I-V, respectively. 12 H 12 ] 2- , closo-[CB 11 H 12 ] - , closo-[C2B 10 H 11 ] - The anion of formula III is an example of closo-[CB 10 H 11 ] - is shown as a 1,2 dicarba species, it will be understood that such closo icosahedral dicarba species may alternatively be 1,7- or 1,12-dicarba. More generally, it will be understood that the requisite carbon atoms in anionic formulae III, IV, and V may occupy any possible position in the boron cluster framework. Also, non-hydrogen substituents, if present in the boron cluster anion, may be attached at any position in the boron cluster framework and, where applicable, at a vertex occupied by boron or carbon.
[0022] In some embodiments, the electrolyte composition exhibits no phase transitions as measured by DSC below 80° C. and standard pressure.
[0023] In some embodiments, the electrolyte composition has a solid state of 10 -10The soft solid electrolyte of the present disclosure exhibits an ionic conductivity of more than 1000 S / cm. It should be noted that the soft solid electrolyte of the present disclosure is substantially softer than most of the solid electrolytes of the prior art. For example, the elastic modulus of a typical sulfide solid electrolyte is about 26 gigapascals (GPa). In contrast, a 1:1 molar ratio LiCB9H 10 :LiCB 11 H 12 Pyr14:CB9H with 80% metal salt 10 A soft solid electrolyte with a solid matrix of LiCB exhibits an elastic modulus (an index of hardness) of only 0.214 GPa. 11 H 12 Pyr14:CB with 45% metal salt 11 H 12 A soft solid electrolyte having a solid matrix of only 2.36 GPa has an elastic modulus of only 2.36 GPa. Thus, in various embodiments, the electrolyte composition can have an elastic modulus of less than about 10 GPa, or less than about 1 GPa, or less than about 0.5 GPa.
[0024] The electrolyte composition may also contain a metal salt comprising a metal cation and an anion. The anion associated with and / or derived from the metal salt may hereinafter be referred to as the "metal salt anion." The metal salt is generally selected based on the electrochemistry of the battery in which the electrolyte composition is used. In various variations, the metal cation is Li + , Na + , Mg 2+ , Ca 2+ , or any other electrochemically suitable cation.
[0025] In some embodiments, the metal salt anion can be any of the boron cluster anions of the types described above. In some such embodiments of the electrolyte, the boron cluster anion of the metal salt can be the same as the boron cluster anion of the soft solid electrolyte, and in some embodiments, the two boron cluster anions can be different. In other variations, the metal salt anion can be any anion suitable for use in battery chemistry, such as TFSI, BF4, PF6, or FSI.
[0026] The solid matrix is generally doped with a metal salt to form the electrolyte composition. Doping can be done by achieving intimate contact between the matrix salt and the doping salt. One way to achieve this is by dissolving the dopant salt in a molten organic salt matrix (melt pouring). Another way is by dissolving all the components in a solvent, mixing, and removing the solvent to yield a solid material. It should be noted that material conditioning by hand milling or ball milling before or after melt pouring can be applied.
[0027] In some embodiments, the electrolyte composition contains a metal salt present in a molar ratio to the solid matrix ranging from about 1:100 to about 100:1. More preferably, in some embodiments, the electrolyte composition contains a metal salt present in a molar ratio to the solid matrix ranging from about 5:100 to about 1:1.
[0028] 2A and 2B show the soft solid matrix (solid matrix) of the present disclosure, Pyr14:CB 11 H 12 , and P2226:CB 11 H 12 1 shows plots of differential scanning calorimetry (DSC) data for 1. Note that no phase transitions are observed below 100° C. and 95° C., respectively.
[0029] Figure 3 shows the closo-[CB 11H 12 ] - 2A and 2B are plots of ionic conductivity for neat solid matrices of the present disclosure with anions. The results of FIG. 3, in conjunction with the results of FIG. 2A and FIG. 2B, clearly show that these materials have appreciable ionic conductivity below 95° C., despite not having a phase transition below 95° C.
[0030] Figure 4 shows the LiCB 11 H 12 N2224:CB doped with 11 H 12 1 is a plot showing the conductivity at various temperatures and two applied pressures for 1000 .mu.m. The electrolyte compositions disclosed are soft solids, and the "softness" of these compositions is quantified based on the amount of pressure required to obtain maximum ionic conductivity (i.e., harder materials generally require higher applied pressure to achieve maximum conductivity). In this regard, solid electrolytes are typically formed into a desired shape by compacting granular or powdered solid electrolyte, for example, in a die press. Harder materials require higher pressure to achieve sufficient compression and particle contact, whereas softer materials are sufficiently compacted with lower pressure.
[0031] The results in FIG. 4 show that the cells with electrolyte pressed at 1 ton pressure show stable data within 2 cycles at all temperatures. At 3 ton applied pressure, the conductivity at the second cycle is slightly less than that at the first cycle. These results show that a low pressure of 1 ton is sufficient to achieve good particle-particle contact for optimal conductivity, clearly demonstrating the softness of the electrolyte composition of the present disclosure. In comparison, 1 ton pressure is about 1 / 4 the pressure required to make good contacts for prior art Li sulfide solid electrolytes.
[0032] Figure 5 shows the LiCB 11 H 12 Pyr14:CB doped with 11 H12 5 is a plot of ionic conductivity at 125° C. with an inset of a photograph of the soft electrolyte. The electrolyte composition of FIG. 5 is prepared by mixing the components at 125° C. for 15 minutes, followed by cooling to room temperature to produce a solid material. The solid material is then hand milled with a mortar and pestle. The solid powder obtained by this operation is converted into round pellets (shown in the inset of FIG. 5) by applying 3 tons of pressure in a die press. The results clearly show that very high ionic conductivity can be obtained with the electrolyte composition of the present disclosure without the need for a phase transition. In addition to the high Li conductivity, the absence of grain boundaries is evident as evidenced by the transparency of the sample. Also, a very high Li ion mobility of 0.86 has been measured for this material (data not shown); this value far exceeds the values (less than 0.5) of all known soft materials, such as polymers and all other OIPC type materials.
[0033] Figure 6 shows Pyr14:CB9H 10 or Pyr14:CB 11 H 12 LiCB9H in a 1:1 molar ratio as the Li salt in 10 :LiCB 11 H 12 6 is a plot of the ionic conductivity of different soft electrolytes of the present disclosure having a melted state of 0.1 to 1.0 mol / L and a melted state of 0.1 to 1.0 mol / L. The composition of FIG. 6 was prepared by mixing the ingredients by hand milling, followed by mixing in the molten state for 24 hours, followed by cooling to room temperature to produce a solid material. The solid material was hand milled with a mortar and pestle to produce a solid powder. The electrolyte was formed by applying 3 tons of pressure in a die press. It should be noted that the conductivity of the resulting material is high compared to the prior art solid electrolyte, lithium phosphorus sulfide (LPS). Additionally, it should be noted that LPS particles require at least 4 tons of pressure to obtain beneficial conductivity, further demonstrating the softness of the electrolyte composition of the present disclosure.
[0034] The above description relates to what are presently considered to be the most practical embodiments. However, it should be understood that the present disclosure is not limited to these embodiments, but rather is intended to encompass various modifications and equivalent arrangements that fall within the spirit and scope of the claims of this application. The claims of this application should be accorded the broadest interpretation so as to encompass all such modifications and equivalent structures as are permitted by law. The invention according to the present disclosure includes the following aspects. <Aspect 1> 1. An electrolyte composition for a secondary electrochemical cell comprising: formula G p A soft solid matrix (solid matrix), represented by A, where: G is an organic cation selected from the group consisting of: Ammonium and phosphonium having a plurality of organic substituents, each of the organic substituents being independently selected from the group consisting of: (i) a linear, branched, or cyclic C1 to C8 alkyl group or fluoroalkyl group; (ii) a C6 to C9 aryl or fluoroaryl group; (iii) a linear, branched, or cyclic C1 to C8 alkoxy or fluoroalkoxy group; (iv) a C6 to C9 aryloxy group or a fluoroaryloxy group; (v) an amino group; and (vi) a substituent combining two or more of (i) to (v); wherein at least one organic substituent of said plurality of organic substituents is different from at least one other organic substituent of said plurality of organic substituents; p is 1 or 2; and A is a boron cluster anion; and A metal salt containing a metal cation and a metal salt anion. <Aspect 2> 2. An electrolyte composition according to embodiment 1, which is: The boron cluster anion A is represented by the formula [B y H (y-z-i) R z X i ] 2- , [CB (y-1) H (y-z-i) R z X i ] - 、[C 2 B(y-2) H (y-t-j-1) R t X j ] - 、[C 2 B (y-3) H (y-t-j) R t X j ] - , or [C 2 B (y-3) H (y-t-j-1) R t X j ] 2- where: y is an integer ranging from 6 to 12; (z+i) is an integer ranging from 0 to y; (t+j) is an integer ranging from 0 to (y-1); X is F, Cl, Br, I, or a combination thereof; and R contains any of a linear, branched, or cyclic C1 to C18 alkyl group or fluoroalkyl group; an alkoxy group or fluoroalkoxy group; and combinations thereof. <Aspect 3> 3. The electrolyte composition of claim 2, wherein the boron cluster anion A comprises a closo-boron cluster anion. <Aspect 4> The boron cluster anion A is at least closo-[B 6 H 6 ] 2- , closo-[B 12 H 12 ] 2- , closo-[CB 11 H 12 ] - , or closo-[C 2 B 10 H 11 ] - The electrolyte composition of embodiment 2, comprising one of: <Aspect 5> The electrolyte composition of embodiment 1, wherein the metal salt anion comprises a boron cluster anion that is independent of: Formula [B y H (y-z-i) R z X i ] 2- , [CB (y-1) H (y-z-i) R z X i ] - 、[C 2 B (y-2) H (y-t-j-1) R t X j ] - 、[C 2 B (y-3) H (y-t-j) R t X j ] - , or [C 2 B (y-3) H (y-t-j-1) R t X j ] 2- A boron cluster anion A represented by: y is an integer ranging from 6 to 12; (z+i) is an integer ranging from 0 to y; (t+j) is an integer ranging from 0 to (y-1); X is F, Cl, Br, I, or a combination thereof; and R contains any of a linear, branched, or cyclic C1 to C18 alkyl group or fluoroalkyl group; an alkoxy group or fluoroalkoxy group; and combinations thereof. <Aspect 6> 6. The electrolyte composition of embodiment 5, wherein the metal salt anion is a closo-boron cluster anion. <Aspect 7> 6. The electrolyte composition of embodiment 5, wherein the boron cluster anion, A, of the soft solid matrix and the boron cluster anion of the metal salt comprise different anions. <Aspect 8> 6. The electrolyte composition of embodiment 5, wherein the boron cluster anion, A, of the soft solid matrix and the boron cluster anion of the metal salt comprise the same anion. <Aspect 9> The metal salt anion is at least one of closo-[B 6 H 6 ] 2- , closo-[B 12 H 12 ] 2- , closo-[CB 11 H 12 ] - , or closo-[C 2 B 10 H 11 ] - 6. The electrolyte composition of embodiment 5, comprising one of: <Aspect 10> The metal salt anion is selected from the group consisting of at least: (fluorosulfonyl)imide (FSI); bis(trifluoromethanesulfonyl)imide (TFSI); PF 6 ; and B.F. 4 2. The electrolyte composition of embodiment 1, comprising one of the anions. <Aspect 11> 2. The electrolyte composition of embodiment 1, wherein the solid matrix contains at least two different organic cations. <Aspect 12> 1. An electrolyte composition for a secondary electrochemical cell comprising: formula G p A soft solid matrix (solid matrix), represented by A, where: G is an organic cation selected from the group consisting of: Ammonium and phosphonium having a plurality of organic substituents, each of the organic substituents being independently selected from the group consisting of: (i) a linear, branched, or cyclic C1 to C8 alkyl group or fluoroalkyl group; (ii) a C6 to C9 aryl or fluoroaryl group; (iii) a linear, branched, or cyclic C1 to C8 alkoxy or fluoroalkoxy group; (iv) a C6 to C9 aryloxy group or a fluoroaryloxy group; (v) an amino group; and (vi) a substituent combining two or more of (i) to (v); p is 1 or 2; and A is a boron cluster anion; and a metal salt containing a metal cation and a metal salt anion; Here, the electrolyte composition has a composition content of 10 -10 It has an ionic conductivity of over 100 S / cm. <Aspect 13> The metal cation is Li+ , Na + , Mg 2+ , Ca 2+ 13. The electrolyte composition of embodiment 12, selected from the group consisting of: <Aspect 14> The metal salt is Li(CB 11 H 12 ), Li(CB 9 H 10 13. The electrolyte composition of embodiment 12, comprising: <Aspect 15> 13. The electrolyte composition of embodiment 12, wherein G contains an ammonium cation. <Aspect 16> 13. The electrolyte composition of embodiment 12, wherein G contains a phosphonium cation. <Aspect 17> 13. The electrolyte composition of embodiment 12, wherein G contains a pyrrolizinium or piperidinium cation. <Aspect 18> 13. The electrolyte composition of embodiment 12, wherein G contains a DEME cation. <Aspect 19> 13. The electrolyte composition of embodiment 12, wherein the metal salt is uniformly distributed throughout the solid matrix. <Aspect 20> 13. The electrolyte composition of embodiment 12, wherein the metal salt is present in a molar ratio to the solid matrix in the range of about 1:100 to 100:1.
Claims
1. Formula G p A soft solid matrix (solid matrix), represented by A, where: G is an organic cation selected from the group consisting of: Ammonium and phosphonium having a plurality of organic substituents, each of the organic substituents being independently selected from the group consisting of: (i) a linear, branched, or cyclic C1 to C8 alkyl group; (ii) a linear, branched, or cyclic C1 to C8 alkoxy group; wherein at least one organic substituent of said plurality of organic substituents is different from at least one other organic substituent of said plurality of organic substituents; p is 1 or 2; and A is a boron cluster anion; and Metal salts containing metal cations and metal salt anions 1. An electrolyte composition for a secondary electrochemical cell comprising: the electrolyte composition has an elastic modulus of less than 10 GPa; the electrolyte composition comprises a metal salt present in a molar ratio to the solid matrix in the range of 5:100 to 1:1; The boron cluster anion is Boranes having 6-12 boron atoms with a total charge of −2; Carboranes having one carbon and 5-11 borons in a cluster structure with a total charge of −1; and Carboranes having two carbon atoms and 4 to 10 boron atoms in a cluster structure with a total charge of -1 or -2; and the boron cluster anion contains at least one of closo-[B 6 H 6 ] 2− , closo-[B 12 H 12 ] 2− , closo-[CB 11 H 12 ] − , or closo-[C 2 B 10 H 11 ] − ; Electrolyte composition.
2. 2. The electrolyte composition of claim 1, wherein the metal salt anion comprises a boron cluster anion independent of: Formula [B y H (y-z-i) R z X i ] 2- , [C.B. (y-1) H (y-z-i) R z X i ] - [C 2 B (y-2) H (y-t-j-1) R t X j ] - [C 2 B (y-3) H (y-t-j) R t X j ] - , or [C 2 B (y-3) H (y-t-j-1) R t X j ] 2- A boron cluster anion A represented by the formula: y is an integer ranging from 6 to 12; (z+i) is an integer ranging from 0 to y; (t+j) is an integer ranging from 0 to (y−1); X is F, Cl, Br, I, or a combination thereof; and R contains any of the following: a straight chain, branched chain, or cyclic C1 to C18 alkyl group or fluoroalkyl group; an alkoxy group or fluoroalkoxy group; and combinations thereof.
3. 3. The electrolyte composition of claim 2, wherein the metal salt anion is a closo-boron cluster anion.
4. 3. The electrolyte composition of claim 2, wherein the boron cluster anion, A, of the soft solid matrix and the boron cluster anion of the metal salt comprise different anions.
5. 3. The electrolyte composition of claim 2, wherein the boron cluster anion, A, of the soft solid matrix and the boron cluster anion of the metal salt comprise the same anion.
6. The metal salt anion is at least closo-[B 6 H 6 ] 2- , closo-[B 12 H 12 ] 2- , closo-[CB 11 H 12 ] - , or closo-[C 2 B 10 H 11 ] - The electrolyte composition of claim 2, comprising one of:
7. The electrolyte composition has an elastic modulus of less than 1 GPa and the metal salt anion is selected from the group consisting of at least: (fluorosulfonyl)imide (FSI); bis(trifluoromethanesulfonyl)imide (TFSI); PF 6 and BF 4 10. The electrolyte composition of claim 1 comprising one of the anions:
8. The electrolyte composition of claim 1 , wherein the solid matrix contains at least two different organic cations.
Citation Information
Patent Citations
Electrodes with magnesium nanoparticles, and electrochemical cells with electrodes
JP2016018786A
Artificial SEI transplantation
JP2018200873A
Preparation of ionic liquids based on boron clusters
JP2019053979A
Ambient temperature superionic conducting salt and process for making ambient temperature superionic conducting salt
US20160372786A1
Ionic liquids for rechargeable magnesium battery
US9455473B1